(untitled) (Annual of the Faculty of Philosophy in Skopje, 2007)
During the Vllth century relationships between Byzance and the Slavs from the areas around Salonica were on turnover. The Slavs endeavored to remove byzantinian rule from its only one military base in Macedonia.. During those activities Slavs acted as an alliance of several tribes. In order to strenght their force Slavs needed some ally, in 618 a. d. they were supported by the Avars. Byzantinian successful military operations against Slavs, brought an peace agreement between the contested sides. As a result of these agreement, probably, „rex Prebond“ was recognized for a „King of his Slavs ”. Prebond, similary to Teodrich the Great, pledge himself to act in direction for strenghting of the authority of the central government in Macedonia. After some time Prebond was suspected that make some“evil” plans about Salonica. During his stay in abovementioned city he was captured and send in Constantinople. After this event a delegation, composed by distinguished Salonica ’s citiziens and representatives of Slavs, vi-sited the Byzantinian Emperor in ored to negotiate for liberating of Prebond. All of these show that there were regular relationships between two political subjects-Byzance and Slavs.